2021
DOI: 10.1109/lwc.2020.3020116
|View full text |Cite
|
Sign up to set email alerts
|

5G Synchronization, Positioning, and Mapping From Diffuse Multipath

Abstract: 5G mmWave communication systems have the potential to jointly estimate the positions of user equipment (UE) and mapping their propagation environments using a single base station. But such potential depends on the characteristics of the reflecting surfaces, such as a deterministic specular nature, a stochastic diffuse/scattering nature, or a combination of both. In this letter, we proposed a 5G positioning and mapping algorithm with unknown orientation and clock bias for single-bounce diffuse multipath channel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 21 publications
0
12
0
Order By: Relevance
“…The transition matrix in (39) indicates that the two states q u and q v in the transition process have only two same CVTs in specified place, which will ensure the relativity in the transition process according to the observation space defined in (35).…”
Section: ) Transition Matrixmentioning
confidence: 99%
See 1 more Smart Citation
“…The transition matrix in (39) indicates that the two states q u and q v in the transition process have only two same CVTs in specified place, which will ensure the relativity in the transition process according to the observation space defined in (35).…”
Section: ) Transition Matrixmentioning
confidence: 99%
“…Our framework also includes wake-up positioning and synchronization 1 aided by radio geometrization, which provides an accurate initial position and time synchronization input for cooperative SLAM. Though the works [20,[35][36][37] also consider synchronization under Channel-SLAM framework, the information of reflecting surfaces is not considered together in their synchronization bias estimation process. This also makes it more robust to satellite-signal conditions that typically impede accurate GPS-based localization in real-life situations, such as the presence of high-rise buildings or other obstructions.…”
Section: Introductionmentioning
confidence: 99%
“…Although the specular MPCs are the ones contributing more to the overall channel gain and exploited in the localization process, the diffuse MPCs can also be used for increasing the localization accuracy. Recently, it was demonstrated that the localization of a TN can be conducted even in the absence of the DPCs and specular IPCs [176,177]. Furthermore, it was demonstrated that exploiting the diffuse IPCs improves not only the localization accuracy but also the synchronization [157].…”
Section: ) Exploitation Of Multipath Componentsmentioning
confidence: 99%
“…Building on this, we present a positioning and mapping method that accurately localizes the user and maps the environment by exploiting the diffuse multipath, rather than considering it as a disturbance. As an extension, [23] provides insights into cases not covered by this paper, namely synchronization and orientation estimation are important in practice. Our main contributions are the following:…”
Section: Introductionmentioning
confidence: 99%